The gut microbiota changed by ketogenic diets contribute to glucose intolerance rather than lipid accumulation - Li, Wei; Gong, Mengxue; Wang, Zhiyi; Pan, Han; Li, Yue; Zhang, Chenhong (Frontiers in Endocrinology, 2024)
The ketogenic diet (KD) is a popular option for managing body weight, though its influence on glucose and lipid metabolism was still inconclusive. Gut microbiota is modulated by dietary pattens and has been associated with the changes of metabolic homeostasis induced by KD. Here, we found that two types of KDs, KD1 (8.8% carbohydrate, 73.4% fat, 17.9% protein, 5.7 kcal/g) and KD2 (0.4% carbohydrate, 93.2% fat, 6.4% protein, 6.7 kcal/g), induced changes of gut microbiota and its metabolites, contributing to glucose intolerance but not lipid accumulation in mice. Following a 2week intervention with KDs, mice fed on KD1 displayed symptoms related to obesity, whereas KD2fed mice exhibited a decrease in body weight but had severe hepatic lipid accumulation and abnormal fatty acid metabolism, while both KDs led to significant glucose intolerance. Compared to the mice fed on a standard chow diet, the conventional mice fed on both KD1 and KD2 had significant shifted gut microbiota, lower levels of short chain fatty acids (SCFAs) and composition alteration of cecal bile acids. By using an antibiotic cocktail (ABX) to deplete most of the gut microbiota in mice, we found the disturbances induced by KDs in lipid metabolism were similar in the ABX-treated mice to their conventional companions, but the disturbances in glucose metabolism were absent in the ABX-treated mice. In conclusion, these findings suggest that ketogenic diets disrupted glucose and lipid metabolism, at least in mice, and highlight the gut microbial culprits associated with KD induced glucose intolerance rather than lipid accumulation.